Knowledge, Attitudes, and Practices (KAP) About Antibiotic Use in Hemodialysis Patients with Chronic Kidney Disease and Their Household Contacts, Medellín-Colombia (2023)
ABSTRACT: Purpose: The lack of knowledge and the excessive and inappropriate use of antibiotics are some of the causes of bacterial resistance. Hemodialysis patients have a high consumption of antibiotics and are constantly cared by their household contacts. This population circulates between hospital and community and are a model to study knowledge regarding bacterial resistance and antibiotic use in these settings. This study describes the knowledge, attitudes and practices (KAP) about antibiotic use and bacterial resistance in hemodialysis patients and their household contacts in Medellín-Colombia. Patients and Methods: A cross-sectional descriptive study was conducted on hemodialysis patients from a renal unit associated with a hospital in Medellín-Colombia, and their household contacts between May 2019 and March 2020. A KAP instrument was applied to participants during home visits. The KAP regarding antibiotic use were characterized, and a content analysis of open questions was made. Results: A total of 35 hemodialysis patients and 95 of their household contacts were included. Of participants, 83.1% (108/130) did not correctly identify the situations in which antibiotics should be used. Likewise, a gap in knowledge about antibacterial resistance was evidenced thanks to the emerging categories in content analysis. Regarding attitudes, 36.9% (48/130) of the participants discontinued antibiotic treatment when they felt better. Additionally, 43.8% (57/130) agree to keep antibiotics in their home. Finally, it was found that it is usual for pharmacists and family members to recommend or sell antibiotics without prescription; likewise, pharmacies were the most popular place to acquire these medications. Conclusion: This study identified gaps in KAP regarding the use of antibiotics and bacterial resistance in hemodialysis patients and their household contacts. This allows focusing education strategies in this regard, in order to increase awareness about the correct use of antibiotics and the consequences of bacterial resistance and to improve prevention actions in this vulnerable population.